Comorbid medical conditions present in pediatric subjects at the time of diagnosis of familial hypercholesterolemia. - Arumugham, Aringha Shree; Zhang, Xiao; Judson, Gwen; Peterson, Amy L. (Journal of Clinical Lipidology, 2026)
Heterozygous familial hypercholesterolemia (HeFH) is a common autosomal dominant disorder, and adults with HeFH can have other cardiometabolic risk factors that increase the risk of events. Recent studies have reported relatively low rates of these risk factors among children with HeFH. Compare cardiometabolic risk factors among children with and without HeFH presenting to a pediatric lipid clinic. We conducted a retrospective chart review study of subjects who presented to the pediatric lipid clinic in a single institution between January 1, 2011, and October 31, 2024. Among subjects with HeFH, 31.6% had body mass index percentile in the obese range, 4.1% had diabetes, and 6.7% had hypertension compared with 56.5% with obesity, 4.7% with diabetes, and 10.6% with hypertension among subjects without HeFH. In this US-based cohort, children with HeFH had a higher prevalence of cardiometabolic comorbidities compared with other populations. Health care providers should screen for and treat these conditions among children at high risk for premature atherosclerotic cardiovascular disease. • Children with familial hypercholesterolemia are thought to have a low prevalence of risk factors like hypertension, obesity, and diabetes. • 6.7% of pediatric patients with familial hypercholesterolemia had hypertension, 4.1% had diabetes, and 31.6% had obesity. • Clinicians are encouraged to screen pediatric patients with familial hypercholesterolemia for these comorbidities.